Copper-catalyzed coupling of anthranils and α-keto acids: direct synthesis of α-ketoamides. Issue 24 (29th May 2019) - Li, Ping-Gui; Zhu, Hao; Fan, Min; Yan, Cheng; Shi, Kai; Chi, Xi-Wen; Zou, Liang-Hua
Abstract : Copper-catalyzed coupling of α-keto acids with anthranils is reported for the synthesis of α-ketoamides bearing an aldehyde group via N–O/C–O bond cleavages and C–N bond formation. Abstract : Copper-catalyzed coupling of α-keto acids with anthranils is reported for the synthesis of α-ketoamides. This process involves N–O/C–O bond cleavages and C–N bond formation. Furthermore, the decarboxylation of α-keto acids can be successfully suppressed under redox-neutral conditions.